Variability for cassava root yield and yield components among half-sib cassava progenies - Codjia, E.D.; Olasanmi, B.; Udemba, I.O.; Rabbi, I.Y. (Informa UK Limited, 2025)
Dry root yield (DRY) should be highly considered in cassava breeding programs as it plays a key role in food industries. One hundred and forty-two cassava genotypes developed from open-pollinated crosses and 3 national check varieties, TMS 07/0593, TMS 30572 and TMS 30555 were assessed for root yield and yield components over 2 years in Ibadan, Nigeria. Data on number of storage roots/plant (SRN), fresh root yield (FRY), dry matter content (DMC), and harvest index (HI) were subjected to a combined analysis of variance (ANOVA) over the two seasons. There were highly significant variations among the genotypes for all the evaluated attributes. The FRY varied from 4.83 to 37.23 t ha−1, while HI and DMC ranged from 0.21 to 0.65 and 11.37% to 43.92%, respectively. Four genotypes, namely UIC-17-282, UIC-17-1677, UIC-17-325, and UIC-17-2009 had higher DRY of 11.53, 11.03, 10.10, and 10.03 t ha−1, respectively, than the check varieties. The adoption of the selection index (SI) approach enabled the identification of the top 13 genotypes which outperformed the national checks with SI ranging between 29.1 and 45.0. High dry root-yielding genotypes identified in our study are suitable candidates for release to farmers; and as parents for further enhancement of cassava for DRY in West Africa. Findings from this research have broader implications for cassava improvement efforts for high dry root productivity.